Taxonomic revision of the South Asian River dolphins (Platanista): Indus and Ganges River dolphins are separate species. Issue 3 (23rd March 2021) - Braulik, Gill T.; I. Archer, Frederick; Khan, Uzma; Imran, Mohammad; Sinha, Ravindra K.; Jefferson, Thomas A.; Donovan, Carl; Graves, Jeff A.
Abstract: South Asian river dolphins ( Platanista gangetica ) are among the most endangered of the world's cetaceans. The two subspecies in the family Platanistidae, Indus, and Ganges river dolphins ( P. g. minor and P. g. gangetica ), are both threatened by dams and barrages, declining river flows, fisheries bycatch, and pollution. We examine differences in external and skull morphology between dolphins in each river system to clarify their taxonomic status. Skulls from each river system could easily be differentiated using diagnostic differences in the shape of the frontal bones behind the nasals. This feature was present in all individuals irrespective of size, age, and sex. Ganges river dolphins are sexually dimorphic with females larger than males, but there was no evidence of dimorphism in the small sample of Indus river dolphins. There were no mitochondrial DNA haplotypes shared between the two river systems, and five fixed differences suggested a long‐term (approximately 0.55 million years) absence of gene flow. Diagnosable differences in morphological and genetic characteristics indicate long‐term reproductive as well as geographic isolation of Indus and Ganges river dolphins. We conclude that Indus and Ganges river dolphins should each be recognized as distinct species, and elevate the Indus subspecies, Platanista gangetica minor, to species level, Platanista minor Owen, 1853. Formal redescriptions are provided for both species.